Policy implications of utilizing indigenous tree species as agroforestry systems in Himalayan states of India: Case study of Uttarakhand. (November 2017) - Phondani, P.C.; Maikhuri, R.K.; Rawat, L.S.; Jugran, A.; Bhatt, A.; Bisht, N.S.
Abstract: Energy supply from the biomass of indigenous tree species in agroforestry systems continues to be an area of great interest among researchers world over to generate fundamental data and innovative ideas for developing appropriate policies, guidelines and legislation. Among the land use systems, agroforestry is recognized as superior land management system having potential to deliver sustainable biomass and energy supply in rural landscape. Present study highlights a comparison of seasonal biomass consumption pattern in terms of fodder and fuelwood energy supply across different village clusters along an altitudinal gradient. The average fuelwood consumption ranged between 242 ± 22 to 373 ± 23 kg/capita/year and fodder consumption ranged between 154 ± 17 to 463 ± 14 kg/unit/year. However, the energy value of fuelwood and fodder consumption ranged between 2160 ± 242 to 7317 ± 234 MJ/kg. The study demonstrated that the fuelwood and fodder consumption was significantly greater (p < 0.05) in winter (lean period) as compared to that in summer and monsoon seasons. The results of this study are valuable to policy planners to improve the current policies for sustainable biomass energy supply in the Himalayan context through utilization of indigenous tree species in agroforestry systems. Highlights: Biomass consumption and energy value was assessed along an altitudinal gradient. Tree biomass is a prime source to meet domestic energy demand in rural landscape. Contribution of agroforestry in supply bioenergy to rural people was estimated. An integrated framework in relation to bioresource utilization was developed. Advocated policy recommendations and guidelines for bioenergy legislation.